Contributions to sustainable development, with the recovery of paramo ecosystems through the study of frailejones germination - Prieto, Nubia Edith Céspedes; Buitrago, Camila Alexandra Vargas; Benavides, Julian David Lara; Cubillos, Julio Cesar (Journal of Posthumanism, 2024)
The recovery of paramo ecosystems is a contribution to environmental sustainability because the knowledge for the germination, development and growth of frailejón leads to revegetation and with them the recovery of paramo ecosystems is a challenge that requires research processes that allows the recovery of the Colombian moors, especially with the Espeletia killipii, a species at risk of extinction and essential for the retention and generation of water sources. The results of this research reveal procedures that lead to results with high performance in germination with specific substrates